2020
DOI: 10.18438/eblip29758
|View full text |Cite
|
Sign up to set email alerts
|

Textbook Alternative Incentive Programs at U.S. Universities: A Review of the Literature

Abstract: Objective – This article reviews current literature on incentive grant programs for textbook alternatives at universities and their libraries. Of particular interest in this review are common patterns and factors in the design, development, and implementation of these initiatives at the programmatic level, trends in the results of assessment of programs, and unique elements of certain institutions’ programs. Methods – The review was limited in scope to studies in scholarly and professional publications of text… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…One type of work that is increasingly common on campuses are OER, which are frequently supported by financial incentive or stipend programs (Alpi, K., et al, 2017;Rigling & Cross, 2018;Lierman, 2020). A 2020 report from the New England Board of Higher Education found that several institutions both public and private in its region are granting faculty seed money to create and integrate OER into their courses (Gumb, 2020).…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…One type of work that is increasingly common on campuses are OER, which are frequently supported by financial incentive or stipend programs (Alpi, K., et al, 2017;Rigling & Cross, 2018;Lierman, 2020). A 2020 report from the New England Board of Higher Education found that several institutions both public and private in its region are granting faculty seed money to create and integrate OER into their courses (Gumb, 2020).…”
Section: Review Of the Literaturementioning
confidence: 99%
“…A 2020 report from the New England Board of Higher Education found that several institutions both public and private in its region are granting faculty seed money to create and integrate OER into their courses (Gumb, 2020). A more geographically diverse study was conducted in 2020 and found that textbook incentive programs have been implemented across a variety of institutions in the U.S. and have a significant positive impact on student savings and pedagogical innovation (Lierman, 2020). While financial incentives alone are rarely the sole motivating factor for faculty to participate in these programs (Coleman-Prisco, 2016;Todorinova & Wilkinson, 2020;Hollister, C.V & Patton, J., 2021), the financial support can create uncertainty about copyright ownership given the provision of "unusual support".…”
Section: Review Of the Literaturementioning
confidence: 99%